The case of the Limehouse laundry - Read, Anthony; Frankland, David (London : Walker Books, 2007)
When their very own Rosie disappears, Sherlock Holmes' Baker Street Irregulars must rescue her and the other girls who have been kidnapped by Chinese criminals working for Professor Moriarty.
Keywords: Child labour -- Fiction; Detective and mystery fiction